Consistency analysis of Kappa angle measurement by Pentacam and Keratron Scout - Jiao Zhao (Guoji Yanke Zazhi, 2019)
AIM: To investigate the repeatability and agreement of Pentacam Front Section Analyzer and Keratron Scout Corneal Topographer in measuring Kappa angle. METHODS: Totally 69 patients were randomly selected from Ophthalmology Department of Leshan People's Hospital. Three readings were taken by the same examiner. Results were recorded in(X, Y)coordinates format and assessed by intraclass correlation coefficient(ICC), Cronbach's Alpha Coefficient, t-test, Pearson correlation analysis and bland-altman analysis. RESULTS: Both instruments showed excellent repeatability in Kappa angle assessment. The results significantly correlated(X value: r=0.90, P<0.01; Y value: r=0.91, P<0.01), however, no significant difference were found between the two instruments. The widest 95% LoA was -0.11-0.14mm for X coordinate and -0.10-0.11mm for Y. CONCLUSION: Pentacam and Keratron Scout showed excellent repeatability and agreement in Kappa angle assessment. The two instruments could aid and verify each other.